ANALYSIS OF BANK HEALTH LEVEL USING RISK-BASED BANK RATING METHOD (RBBR) - Marrida, Dwita; Damayanti, Silvyana Maya (Journal of Business and Management, 2017)
Abstract.The objective of this research was to find out: (1) the healthy level of bank in term of risk profile aspects in2011-2015, (2) the healthy level of bank in term of good corporate governance aspects in 2011 -2015 (3) thehealthy level of bank in term of earnings aspects in 2011-2015, (4) the healthy level of bank in term of capital aspects in 2011-2015, and (5) the healthy level of bank in term of risk profile, good corporate governance, earnings, and capital aspects in 2011-2015. The data were collected through documentation. This research undertook four RBBR factors, risk profile factor through the NPL ratio and LDR, Good Corporate Governance factor, Earning factor through ROA ratio and NIM, and Capital factor through CAR. The result of this research showed that in the periods of 2011-2053, all of the researched banks got predicate as health enough. Risk Profile factor showed bank’s NPL were under 5% and most of bank’s LDR got predicate as health enough. Good Corporate Governance factor showed banks got predicate very good. Earning factor showed bank’s ROA were over 1,5% and banks’ NIM were over 3%. Capital factor showed banks’ CAR were over 12% so that it could fill 8% the minimum of capital availability.Keywords: The Healthy Level of Bank, RGEC Method